Presence and Impact of the Articles on Corporate Social Responsibility in the Different Research Areas - Cuervo Carabel, Tatiana; Repiso, Rafael (SAGE Open, 2023)
The concept of Corporate Social Responsibility (CSR) has been the object of study by the academic world in recent years, however, despite the large number of published works, there are still many gaps in its conceptualization and the implications it has on business management. In this sense, despite the great interdisciplinarity of the concept, a large part of academic production is focused on the field of business, something that has limited the construction of new research perspectives which will allow to continue expanding in knowledge. The objective of this work is to provide evidence of the scientific production developed in the field of CSR that serves as a basis for researchers in making strategic decisions about the orientation of their work, taking into account new perspectives based on the impact generated by the publications in the different research areas. For this, a search of existing publications on the Web of Science (WoS) was carried out. The analysis of the results was developed through the use of the InCites citation analysis tool, which made it possible to evaluate the productivity and performance of the research developed. The results show the existence of research areas with low productivity in the topic under study, but with a high impact of their publications. It is concluded that publication in these research areas should be a priority for researchers, who, by directing their work toward them, might open up new research perspectives and continue to delve into the concept.
Keywords: bibliometric analysis; corporate social responsibility; InCites; research areas; WoS; Scopus; JCR